Efficacy of Oral Appliance Therapy as a First-Line Treatment for Moderate or Severe Obstructive Sleep Apnea: A Korean Prospective Multicenter Observational Study - Byun, Jung-Ick; Kim, Dongha; Ahn, Su-Jin; Yang, Kwang Ik; Cho, Yong Won; Cistulli, Peter A.; Shin, Won Chul (Journal of clinical neurology (Seoul, Korea), 2020)
Responses to oral appliances (OAs) in obstructive sleep apnea (OSA) vary, and have not been fully evaluated in Korean patients. In this study we aimed to determine the efficacy of OAs for the first-line treatment of Korean patients with moderate or severe OSA. This multicenter prospective observational study included 45 patients with moderate or severe OSA that had been newly diagnosed between March 2017 and May 2018 and who underwent OA treatment for 1 month. Questionnaires were completed and polysomnography (PSG) was performed before and after OA treatment. The primary outcome measures were improvement in the absolute apnea-hypopnea index (AHI) and the percentage reduction in the AHI. The secondary outcomes were improvements in the questionnaire scores related to sleep-associated symptoms and PSG parameters. The patients were aged 47.4±12.1 years (mean±SD), only two of them were female, and their AHI at baseline was 29.7±10.9/h. After OA treatment the AHI had reduced by 63.9±25.8%, with the reduction was similar between the patients with moderate OSA and those with severe OSA. Overall 31.1% of the patients achieved a normal AHI (<5/h), and 64.4% had an AHI of ≤10/h after the treatment. The body mass index (BMI) was the most reliable factor for predicting the percentage reduction in the AHI. The OAs also improved the sleep architecture and subjective sleep-related symptoms. The OAs were effective in patients with moderate or severe OSA. The OAs reduced the mean AHI to 63.9% of the baseline value, and this reduction was influenced by the BMI.